Основні причини браку при виводі офсетних СТР пластин - Свиридова, Ю. В. (ХНУРЕ, 2021)
The paper discusses the main causes of rejection in the output of offset CtP plates, a method for checking the plates for the presence of the described defects, as well as possible ways to eliminate them. Most often meetin gs reasons of marriage of the offset CTP plates are related to their mechanical damage, and also with wrong speed of their display.
Keywords: друк; брак